"Catching a Child": giving birth under nomadic conditions. The methods of pre- and postnatal care of the Nenets mothers and babies. Issue 1 (1st January 2019) - Vylka Ravna, Zoia
ABSTRACT: Objectives : The term "Catching a Child" is used by the Tundra Nenets people for the process of giving birth. The author is providing a description of the preparations for giving birth on the tundra in the Nenets nomadic culture, and practice of pre- and postnatal care of mothers and babies. According to the requirements of the child-care system in Russia, the authorities consider the conditions for giving birth in nomadic dwellings in the tundra as unhealthy and unsuitable because they are not considered to meet the acceptable hygienic and safety standards found in a modern well-equipped hospital. Therefore, the official policy is to get as many indigenous Nenets women as possible to give birth in their nearest hospitals and to transport them there by helicopter. Methods : Anthropological research (four field work stages), in-depth interviews, participant observation and questionnaires. Results and conclusions : The Tundra Nenets women are in possession of unique knowledge of pre and postnatal care. This is a system that can be categorised as IKS – indigenous knowledge system. This research area shows the efficiency of the IKS, especially in conditions of climatic changes, which are affecting the infrastructure, transportation and general health-care system in the Arctic.